Superior Management Support and Coffee Introduction Technology on Operational Performance CCT Company - Almerindo Bianco Sequeira; Luciana Andrawina (School of Industrial and System Engineering, Telkom University, 2021)
An important area in the company is the operational field that ensures business operations toimprove the company's operational performance over a certain period. The purpose of this study isto propose a conceptual model for further research on the effect of superior management supportand coffee introduction technology to improve company operational performance. Operationalperformance refers to the company's capability, which is indicated by the aspects of cost, productionvolume, fulfilment of demand, customer handling, process control and quality. A number of datawill be required and collected in this study to test the existing hypothesis models. The data werecollected using a questionnaire that was distributed directly to individual workers in the companywith positive questions on a 6-point measurement scale from strongly agree to strongly disagree.Data processing will be carried out using the SEM-AMOS method. One of the results of operationalperformance is customer focus, which is the orientation of a series of services provided to customersto improve customer satisfaction. The mechanism for eliminating waste and creating added valuefor the company is process control and improvement at every stage of the process in the company.The results of this study present a conceptual model for further research with the aim of knowing theeffect of superior management support, consumer focus, and process control, and coffeeintroduction technology on the operational performance of CCT companies in Timor-Leste.